LncRNA CTBP1-AS2 regulates miR-216a/ PTEN to suppress ovarian cancer cell proliferation - Kaiying Cui; Genhai Zhu (BMC, 2020)
Abstract Background We analyzed TCGA dataset and observed the downregulation of CTBP1-AS2 in ovarian cancer (OC), while the function of CTBP1-AS2 has only been investigated in diabetes and cardiomyocyte hypertrophy, but not in cancer biology. We therefore analyzed the involvement of CTBP1-AS2 in OC. Result We found that CTBP1-AS2 was downregulated in OC and predicted poor survival. CTBP1-AS2 in luciferase activity assay interacted with miR-216a, while overexpression of CTBP1-AS2 and miR-216a had no significant effects on the expression of each other. However, increased expression level of PTEN, a target of miR-216a, was observed after CTBP1-AS2 overexpression. Increased proliferation rate of OC cells was observed after the overexpression of miR-216a. CTBP1-AS2 and PTEN overexpression resulted in the reduced proliferation rate of OC cells and reduced effects of miR-216a overexpression. Conclusion CTBP1-AS2 regulates miR-216a/PTEN to suppress OC cell proliferation.